2020
DOI: 10.1016/j.cam.2020.112713
|View full text |Cite
|
Sign up to set email alerts
|

On an optimal quadrature formula for approximation of Fourier integrals in the space L2(1)

Abstract: This paper deals with the construction of an optimal quadrature formula for the approximation of Fourier integrals in the Sobolev space L (1) 2 [a, b] of non-periodic, complex valued functions which are square integrable with first order derivative. Here the quadrature sum consists of linear combination of the given function values in a uniform grid. The difference between the integral and the quadrature sum is estimated by the norm of the error functional. The optimal quadrature formula is obtained by minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 20 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…2 [a, b] the coefficients of the optimal quadrature formulas (33) have the same forms as derived in [20], where it was shown that for functions with a continuous second derivative the convergence order of this optimal quadrature formula is O(h 2 ).…”
Section: Optimal Quadrature Formulas For the Interval [A B]mentioning
confidence: 99%
See 2 more Smart Citations
“…2 [a, b] the coefficients of the optimal quadrature formulas (33) have the same forms as derived in [20], where it was shown that for functions with a continuous second derivative the convergence order of this optimal quadrature formula is O(h 2 ).…”
Section: Optimal Quadrature Formulas For the Interval [A B]mentioning
confidence: 99%
“…In this section, we deal with the second and third order optimal quadrature formulas only. For the numerical results with the first order optimal quadrature formula, see [20].…”
Section: Application: Ct Image Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation